Pengembangan Media Pembelajaran E-Bookstory Berbasis Powerpoint Untuk Meningkatkan Literasi Dasar Siswa Pada Materi Dongeng: Development of Powerpoint-Based E-Bookstory Learning Media to Improve Students' Basic Literacy on Fairy Tale Material - Nepri Handayani Siregar; Sapri Sapri (Institut Agama Islam Daruttaqwa Gresik, 2025)
The low interest and reading ability of elementary school students, especially at the Addini Islamic Foundation, is a problem that needs to be addressed in this study. This study aims to develop PowerPoint-based e-bookstory learning media as an innovation to improve students’ reading skills in fairy tale material. The subjects of this study were grade II students, with the Research and Development (R&D) method of the 4-D model, which was simplified into the define, design, development, and disseminate phases. The results of the study showed that the e-bookstory media was very feasible to use, with an average validation score of 89%, and its effectiveness was classified as high based on an increase in the N-Gain score of 76%. These findings show that the use of e-bookstory media can significantly increase students’ interest and reading ability and receive very positive responses from teachers and students. The implications of this research indicate that the integration of digital and interactive media in the learning proces such as e-bookstories can be an effective strategy to overcome reading difficulties at the elementary level. Furthermore, this approach can be adopted by educators as a complementary tool to conventional methods, especially in early grade literacy programs. The success of this media also opens opportunities for further innovation in the development of multimedia-based learning tailored to various themes and subjects, thereby supporting the broader goal of improving literacy culture in schools.